Gestão de resíduos sólidos: uma análise em municípios de pequeno porte na região do Médio Alto Uruguai/RS - Knopf, Débora dos Santos (2021)
The present study arises with the objective of analyzing from the creation of the PNRS, the effective application and adherence of this policy by the small municipalities, characterized by up to 20 thousand inhabitants. To this end, the work analyzed the management of solid waste in 4 (four) small municipalities located in the Médio Alto Uruguai region of the state of Rio Grande do Sul. To achieve the proposed objectives a methodology with a qualitative approach was used. Documentary research and semi-structured interviews were conducted with the managers responsible for the solid waste of each municipality, and simultaneously with those responsible for the Consórcio Intermunicipal de Gestão de Resíduos (CIGRES), which the municipalities are consortium with. The results showed that in general, although at a slow pace, small municipalities are evolving with respect to the implementation of the guidelines determined in the PNRS. It was possible to observe several positive aspects resulting from the consortium for the management, disposal and proper final disposal of solid waste. On the positive points, the initiatives of projects for home composting of organic residues stand out, conducting campaigns for the collection of residues such as glass and electronics, partnerships with institutions and cooperatives, investments and improvements in the Consortium, investments in the acquisition of best dumps, among others. On the other hand, there were several difficulties and aspects that can be improved for an effective application of PNRS. The main difficulties encountered relate to problems in the process of collecting and transporting solid waste, the low rate of recycling of waste, the little awareness of the population about solid waste, the lack of financial resources, the little availability of information to the population, the lack of support and greater involvement of managers and leaders, the inefficiency of reverse logistics, among others. Finally, according to the difficulties and potential observed, an improvement proposal for the management of solid waste was elaborated, aiming to contribute to the better disposal and proper disposal of waste, as well as the quality of life of the residents. In addition, the results were satisfactory, since some of the suggestions for proposed improvements were possible to be implemented by the end of the present research.